Development and Maintenance of Epidermal Stem Cells in Skin Adnexa - Mokry, Jaroslav; Pisal, Rishikaysh (International journal of molecular sciences, 2020)
The skin surface is modified by numerous appendages. These structures arise from epithelial stem cells (SCs) through the induction of epidermal placodes as a result of local signalling interplay with mesenchymal cells based on the Wnt-(Dkk4)-Eda-Shh cascade. Slight modifications of the cascade, with the participation of antagonistic signalling, decide whether multipotent epidermal SCs develop in interfollicular epidermis, scales, hair/feather follicles, nails or skin glands. This review describes the roles of epidermal SCs in the development of skin adnexa and interfollicular epidermis, as well as their maintenance. Each skin structure arises from distinct pools of epidermal SCs that are harboured in specific but different niches that control SC behaviour. Such relationships explain differences in marker and gene expression patterns between particular SC subsets. The activity of well-compartmentalized epidermal SCs is orchestrated with that of other skin cells not only along the hair cycle but also in the course of skin regeneration following injury. This review highlights several membrane markers, cytoplasmic proteins and transcription factors associated with epidermal SCs.
Keywords: skin adnexa; epidermis; Epidermis; Stem Cells; epidermal placode; Epidermal Cells; lidé; buněčná diferenciace; epidermální buňky; stem cell; kmenové buňky; kůže; signální transdukce; vlasový folikul; Signal Transduction; Hair Follicle; Skin; Cell Differentiation; hair pigmentation; signalling; keratins; markers; Humans